Doing justice : congregations and community organizing - Jacobsen, Dennis A., 1947- (Minneapolis : Fortress Press, 2017)
Doing Justice introduces people of faith to congregation-based community organizing rooted in the day-to-day struggles and hopes of urban ministry. Drawing from the author's decades of experience in community organizing ministry and skillfully illustrated with examples, Dennis A. Jacobsen weaves theological and biblical warrants for community organizing into concrete strategies for achieving justice in the public arena and discusses fundamental organizing principles like power, self-interest, and agitation. The second, updated edition includes a new preface, forewords, and new sidebars by Gran.
The World as It Is -- The World as It Should Be -- Engaging the Public Arena -- Congregation-Based Community Organizing -- Power -- Self-Interest -- One-on-Ones -- Agitation -- Metropolitan Organizing -- Building and Sustaining an Organization -- Community -- A Spirituality for the Long Haul.
Includes bibliographical references and index.
Keywords: Christian sociology; Community organization -- United States